Peran Pendidikan Dan Bimbingan Konseling Terhadap Pengembangan Dan Validasi Skala Ketahanan Karir - Mudafiatun Isriyah; Yanti Nurhayati; Addahri Hafidz Awlawi; Sukatno Sukatno; Farida Isroani (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to develop and validate a career resilience scale to measure the level of career resilience in adult workers. The study was conducted through quantitative research methods involving 405 adult workers of Mustikatama factory workers in Lumajang, East Java. The developed scale is called CARE-NP (Courage, Adaptability, Resilience, Efficacy, Networking, Proactive) and was validated through content validity, construct validity, and reliability stages. The collected data were analyzed using statistical techniques such as exploratory factor analysis, confirmatory factor analysis, and correlation coefficient. The results showed that the CARE scale met the expected validity and reliability criteria. This study concludes that the CARE scale can be used to measure the level of career resilience in adult workers with good validity and reliability. This study makes an important contribution in expanding the understanding of career resilience and enabling guidance and counseling professionals to provide more effective services in helping individuals build better career resilience.